Maintenance and Counseling of the ECG Machine at the Puskesmas Deket Lamongan in an Effort to Maintain Continuity of Services for the Community - Dyah Titisari; Triwiyanto Triwiyanto; Dwi Herry Handayani (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Some of the problems faced by partners include the EKG machine in the publich health center (Puskesmas) at the Puskesmas Deket, Lamongan, which has a fairly high workload on daily use, considering that the population in the working area of ​​the Deket Health Center is 44,193 people, so maintenance is mandatory to be carried out regularly to maintain sustainability. the function of the tool on the other side of the Deket, Lamongan health center there are no special personnel or technicians who carry out routine and periodic maintenance of the ECG machine. Therefore, community service activities in the form of counseling and assistance for health workers at the Deket Health Center, Lamongan are important so that they can carry out ECG machine maintenance activities independently. Furthermore, for the last 5 years or so, health workers at the Deket Health Center, Lamongan have received less training or workshops related to the maintenance of the ECG machine. As a completion step, it is necessary to carry out implementation steps through methods, namely communicating with the head of the Deket Health Center, Lamongan Regency to prepare for the right day and target participants to receive ECG maintenance counseling activities at partners, provide counseling for health workers or the person in charge ECG so the next step is to carry out maintenance activities together. With the method we propose, partners can learn together in implementing the SOPs that have been delivered during the counseling. Furthermore, lecturers and students regularly provide assistance for partners in carrying out maintenance activities for 7 months so that partners are expected to carry out maintenance activities independently. The results obtained after carrying out community service activities are ECG machine operators can use the machine well. Several problems related to the irregular display of the ECG recording can be resolved properly, after replacing the ECG electrode cable section. Maintenance of electromedical equipment, especially ECG is important to be done regularly so that the ECG machine can be operated at any time.